Rural energy: Power to the community - Njuguna, Paul (Technical Centre for Agricultural and Rural Cooperation, 2008)
Using hydro and solar energy, a village in Kenya now boasts the first hybrid zero emission power supply in the country. The community power centre provides a stable electricity supply and brings internet and mobile phone access to local farmers.